Profile of Critical Thinking Skills and Cultural Literacy of Students in the Basic Chemistry Course - Khaeruman, Khaeruman; Suma, Ketut; Maryam, Siti; Suastra, I Wayan; Nurhidayati, Siti (Universitas Pendidikan Mandalika, 2025)
This study investigates the profile of critical thinking skills and cultural literacy among students in the Basic Chemistry course at the Faculty of Science, Technology, and Applied Sciences, Universitas Pendidikan Mandalika. In the context of globalization and rapid technological advancements, critical thinking and cultural literacy are crucial competencies for facing the challenges of the 21st century and the Fourth Industrial Revolution. Despite the foundational importance of Basic Chemistry in science education, challenges such as conceptual complexity and low student engagement remain prevalent. Employing a descriptive quantitative approach, this research involves students from Chemistry, Biology, Physics, and Mathematics Education programs. Instruments used include critical thinking tests and cultural literacy questionnaires measuring understanding of local cultural values and diversity. Data were collected through tests, questionnaires, and semi-structured interviews and analyzed descriptively using statistical methods. Findings reveal that students exhibit low levels of critical thinking skills and cultural literacy, with strengths in data interpretation and cultural preservation, while weaknesses are evident in identifying relevant information and cultural promotion. These results highlight the need for innovative instructional models integrating local wisdom into the learning process. The proposed Free Inquiry-Based Etnochemistry Model aims to enhance both critical thinking skills and cultural literacy by contextualizing scientific concepts within local cultural practices, offering a holistic solution to contemporary educational demands.